KETIMPANGAN PEMBIAYAAN PENDIDIKAN ANTAR DAERAH DI INDONESIA: KAJIAN LITERATUR TERHADAP DESENTRALISASI FISKAL DAN PEMERATAAN AKSES - Runiasih, Mawar; Ahmad, Masduki (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the disparity in education financing between regions in Indonesia in the context of fiscal decentralization. The main focus is directed at how variations in fiscal capacity and regional governance affect the proportion of education spending and the achievement of access and quality of education services. The method used is a systematic literature review of scientific journals, policy documents, and reports from national and international institutions published in 2015–2025. The analysis was carried out through thematic coding of issues such as the General Allocation Fund (DAU), Special Allocation Fund (DAK), Regional Original Income (PAD), and education indicators such as School Participation Rate (APS), Gross Participation Rate (APK), and National Assessment results (AN). The results of the study show significant disparities in education spending per capita between regions with high and low PAD. Transfer funds from the center have not been fully effective in closing the gap, especially because the allocation scheme is less flexible and there are minimal performance-based incentives. Regions with weak managerial capacity tend to have lower education outcomes. The novelty of this article lies in the development of a conceptual model that links fiscal decentralization, local budget capacity, and the proportion of education spending to equal access and quality of education. This model provides a basis for recommendations for fiscal policies based on performance and real regional needs.